Efektifitas Penegakan Hukum Terhadap Tindak Pidana Prostitusi Online Ditinjau dari Undang-Undang RI Nomor Undang-Undang Nomor 19 Tahun 2016 - Kadarudin; Imelda hasibuan; Nenci (Collegium Studiosum Journal, 2022)
Advances in technology these days can not be denied anymore, almost everyone can access the internet. It is enough to carry out buying and selling transactions online using the internet network. But the ease of internet access is abused by irresponsible parties. One way is to carry out prostitution transactions through the internet network known as online prostitution. Online prostitution or prostitution is the practice of prostitution by using the internet or social media as a means of connecting or a means of communication for pimps, sex workers and their users. The author uses the library research method or literature review. This library research research is to conduct research from library books, magazines, journals and articles and sources from the internet that are relevant to the issues discussed. The amendments to the Laws that are used are RI Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions Law No. 21 of 2007 concerning the Crime of Trafficking in Persons, Law Number 3 of 2002 concerning Child Protection.